2020
DOI: 10.1016/j.isci.2019.100763
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-127 Promotes Anti-microbial Host Defense through Restricting A20-Mediated De-ubiquitination of STAT3

Abstract: The increasing rising of multiple drug-resistant Staphylococcus aureus has become a major public health concern, underscoring a pressing need for developing therapies essentially based on the understanding of host defensive mechanism. In the present study, we showed that microRNA (miR)-127 played a key role in controlling bacterial infection and conferred a profound protection against staphylococcal pneumonia. The protective effect of miR-127 was largely dependent on its regulation of macrophage bactericidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The MRSA strain (USA300) reported by our previous study ( 16 ) was cultured in Luria Bertani broth at 37°C until its stable growth phase, and then collected by centrifugation at 8,000 rpm for 5 min. The bacteria were washed three times with PBS and resuspended to an optical density of 0.8 at 600 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRSA strain (USA300) reported by our previous study ( 16 ) was cultured in Luria Bertani broth at 37°C until its stable growth phase, and then collected by centrifugation at 8,000 rpm for 5 min. The bacteria were washed three times with PBS and resuspended to an optical density of 0.8 at 600 nm.…”
Section: Methodsmentioning
confidence: 99%
“…BALF collection was performed in line with our published procedure with minor modifications ( 16 ). Briefly, we sacrificed the mice by cervical dislocation and exposed the trachea.…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial innate immunity is modulated by miR-127 via the regulation of the A20/STAT3 axis [ 55 ]. A previous study indicated that the expression levels of miR-127 were induced by Staphylococcus aureus ( S. aureus ) infection.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-microbial host defense is mediated by miR-127 via targeting the A20/STAT3 axis [ 55 ]. By using miR-127 mimics and inhibitors, it was confirmed that miR-127 conferred protection against S. aureus pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the upregulation of A20 expression can inhibit apoptosis induced by microglial exosomes ( Chen et al, 2019 ). A20 interacts with RIPK1 through its ZnF7 structural domain to affect caspase-8 protein expression in intestinal epithelial cells, thereby inhibiting their apoptosis ( Liu X. et al, 2020 ). Furthermore, A20 upregulation inhibits intestinal epithelial cell apoptosis in Crohn’s disease ( Zhou et al, 2019 ) by affecting the functions of tumor necrosis factor receptor 1 (TNFR1), TNFR1-associated death domain protein (TRADD) and RIPK1.…”
Section: Introductionmentioning
confidence: 99%